FinTech and financial inclusion in Pakistan: Investigating the mediating role of digital financial literacy and the moderating effect of perceived regulatory support - Idrees, Muhammad Abdullah; Abdel-Razzaq, Assim Ibrahim Mohammad; Ghaffar, Abdul (Edelweiss Applied Science and Technology, 2025)
FinTech enhances financial inclusion by providing easy access to financial services and affordability for the unbanked population. This study aims to examine how the use of FinTech promotes financial inclusion in Pakistan, considering digital financial literacy as an influencing variable and perceptions of support from financial regulations as a moderating factor. The research investigates individual adoption of FinTech and the benefits of easier access to official financial services. Data was collected from 600 users of financial technology in Pakistan and analyzed using PLS-SEM. The findings indicate that trust, quality of service, and security positively influence FinTech usage in Pakistan. FinTech facilitates greater participation of underserved communities in financial services by reducing access costs. The study demonstrates that digital financial literacy bridges the gap between financial technology and broader financial inclusion, with perceptions of supportive regulations further strengthening this relationship. These insights provide valuable guidance for policymakers, regulators, and FinTech businesses operating in Pakistan.